Plasma exchanges for the treatment of severe systemic necrotizing vasculitides in clinical daily practice: Data from the French Vasculitis Study Group. (December 2015) - de Luna, Gonzalo; Chauveau, Dominique; Aniort, Julien; Carron, Pierre-Louis; Gobert, Pierre; Karras, Alexandre; Marchand-Adam, Sylvain; Maurier, François; Hatron, Pierre-Yves; Mania, Alexandre; le Guenno, Guillaume; Bally, Stéphane; et al.
Abstract: The use of plasma exchanges (PLEX) in systemic necrotizing vasculitides (SNV) still need to be codified. To describe indications, efficacy and safety of PLEX for the treatment of SNV, we conducted a multicenter retrospective study on patients with ANCA-associated vasculitis (AAV) or non-viral polyarteritis nodosa (PAN) treated with PLEX. One hundred and fifty-two patients were included: GPA (n = 87), MPA (n = 56), EGPA (n = 4) and PAN (n = 5). PLEX were used for rapidly progressive glomerulonephritis (RPGN) in 126 cases (86%), alveolar hemorrhage in 64 cases (42%), and severe mononeuritis multiplex in 23 cases (15%). In patients with RPGN, there was a significant improvement in renal function compared to baseline value (P < 0.0001), the plateau being reached at month 3 after PLEX initiation, and estimated glomerular filtration rate improved especially as the number of PLEX increased. In patients with alveolar hemorrhage, mechanical ventilation was discontinued in all patients after a median time of 15 days. Patients treated for mononeuritis multiplex showed improvement of severe motor weakness. After a median follow of 22 months, 18 deaths (12%) were recorded, mainly in patients with RPGN and within the first 6 months. Incidence of end-stage renal disease and/or death was similar between groups of different baseline renal function, but was increased in MPO-ANCA compared to PR3-ANCA. Adverse events attributable to PLEX were recorded in 63%. No death occurred during PLEX. This large series describes indications, efficacy and safety of PLEX in daily practice. Randomized controlled studies are ongoing to define optimal indications, PLEX regimen and concomitant medications. Highlights: A significant improvement in renal function was noted, the plateau being reached at month 3 after PLEX initiation. eGFR seems to improve especially as the number of PLEX increases. In patients with alveolar hemorrhage, mechanical ventilation was discontinued in all patients after a median time of 15 days. Patients treated for mononeuritis multiplex showed improvement of severe motor weakness. Incidence of ESRD and/or death was similar between groups of different baseline renal function, but increased in MPO-ANCA.